2021
DOI: 10.1080/23802359.2021.1901626
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of an Endangered freshwater snail Koreoleptoxis nodifila (Caenogastropoda: Semisulcospiridae) from South Korea

Abstract: The mitochondrial genome of the Endangered freshwater snail Koreoleptoxis nodifila (Caenogastropoda: Semisulcospiridae) from South Korea is determined and characterized in detail. It is 15,737 bp in length being composed of 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and one control region. It has a base composition of 31.23% for A, 16.29% for G, 17.84% for C, and 34.64% for T. The phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…At the superfamily level, some superfamilies are recovered monophyletic and supported, often confirming previously published phylogenies, although based on a much more reduced sampling (Choi et al, 2021;Osca et al, 2015;Uribe et al, 2021;Wang et al, 2021). For example, the Conoidea, represented by many mitogenomes covering almost all the family-level diversity of the group, is found monophyletic.…”
Section: Input For Neogastropod Classificationsupporting
confidence: 84%
See 3 more Smart Citations
“…At the superfamily level, some superfamilies are recovered monophyletic and supported, often confirming previously published phylogenies, although based on a much more reduced sampling (Choi et al, 2021;Osca et al, 2015;Uribe et al, 2021;Wang et al, 2021). For example, the Conoidea, represented by many mitogenomes covering almost all the family-level diversity of the group, is found monophyletic.…”
Section: Input For Neogastropod Classificationsupporting
confidence: 84%
“…And even in an era when datasets based on transcriptomes or reduced genomes are becoming more and more common, new mitogenomes are being produced regularly. Furthermore, in gastropods, the publication of a new mitogenome(s) provides often the opportunity to produce a new phylogeny by combining the newly produced mitogenome(s) with previously published ones (Barghi et al, 2016; Choi et al, 2021; Harasewych et al, 2019; Huang et al, 2021; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2019 ; Choi et al. 2021 ), the ML tree in this study showed that the superfamily Cerithioidea was recovered as a monophyletic group (bootstrap probability = 100%). The family Potamididae ( Cerithidea species+ Pirenella pupiformis ) was monophyletic with robust support (100%).…”
supporting
confidence: 53%